(untitled) (Clinics, 2010)
OBJECTIVES: The efficacy of combined lumbar plexus-sciatic nerve blocks was compared to epidural anesthesia in patients undergoing total knee surgery. PATIENTS AND METHODS: The study included 80 American Society of Anesthesiologists (ASA) Physical Status I-III patients (age range 18 to 65) undergoing knee surgery. The patients were randomly divided into one of two groups. Epidural anesthesia was performed in the epidural anesthesia (EA) group (n=40), and the lumbar plexus and sciatic nerves were blockedin the lumbar plexus-sciatic nerve blocks (LPSB) group (n=40). For each patient, onset of sensory and motor block, degree of motor block, sign of sensory block in the contralateral lower limb for the lumbar plexus-sciatic nerve blocks group, success in providing adequate anesthesia, hemodynamic changes, time of first analgesic request, and patient and surgeon satisfaction with the anesthetic technique were recorded. RESULTS: One patient in the epidural anesthesia group and three patients in the lumbar plexus-sciatic nerve blocks group required general anesthesia due to failed block. There were no significant differences between the two groups regarding the success of providing adequate anesthesia. Eight patients in the lumbar plexus-sciatic nerve blocks group developed contralateral spread. The onset of sensory-motor block and the time of the first analgesic request were significantly later in the lumbar plexus-sciatic nerve blocks group than in the epidural anesthesia group. Although there were no significant differences regarding patient satisfaction with the anesthetic technique between the two groups, surgeon satisfaction was significantly higher in the lumbar plexus-sciatic nerve blocks group than in the epidural anesthesia group. CONCLUSION: The lumbar plexus -sciatic nerve blocks provide effective unilateral anesthesia and may offer a beneficial alternative to epidural anesthesia in patients undergoing total knee surgery.